2014
DOI: 10.1038/srep05050
|View full text |Cite
|
Sign up to set email alerts
|

Transposon-mediated targeted and specific knockdown of maternally expressed transcripts in the ascidian Ciona intestinalis

Abstract: Maternal mRNAs play crucial roles during early embryogenesis of ascidians, but their functions are largely unknown. In this study, we developed a new method to specifically knockdown maternal mRNAs in Ciona intestinalis using transposon-mediated transgenesis. We found that GFP expression is epigenetically silenced in Ciona intestinalis oocytes and eggs, and this epigenetic silencing of GFP was used to develop the knockdown method. When the 5′ upstream promoter and 5′ untranslated region (UTR) of a maternal gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…In a previous study, we showed that both eGFP and Kaede can induce MASK 22 . These reporter genes were driven by the cis elements of targeted maternal genes for inducing MASK.…”
Section: Resultsmentioning
confidence: 89%
See 4 more Smart Citations
“…In a previous study, we showed that both eGFP and Kaede can induce MASK 22 . These reporter genes were driven by the cis elements of targeted maternal genes for inducing MASK.…”
Section: Resultsmentioning
confidence: 89%
“…In MASK, the location of the MASK vector in the genome is usually not close to the genomic locus where the target gene is encoded 22 . A factor created from the MASK vector is thus suspected to reach the target gene or its mRNA to suppress it.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations